Recurrent pericarditis as an extra‐intestinal manifestation of ulcerative colitis in a 14‐year‐old girl. Issue 8 (22nd June 2018) - Van Gils, Ann J. M.; van Gijlswijk, Sandra; Taminiau, Jan A. J. M.; Marchau, Fabienne; Van De Vijver, Els
Key Clinical Message: Pericarditis is a known complication of mesalazine in the treatment of ulcerative colitis. This case study illustrates that after diagnostic work‐up, pericarditis should not always be attributed to the use of mesalazine. It may be the presentation of an extra‐intestinal manifestation of ulcerative colitis. Restarting of mesalazine should be considered. Abstract : Pericarditis is a known complication of mesalazine in the treatment of ulcerative colitis. This case study illustrates that after diagnostic work‐up, pericarditis should not always be attributed to the use of mesalazine. It may be the presentation of an extra‐intestinal manifestation of ulcerative colitis. Restarting of mesalazine should be considered.